1979
DOI: 10.1159/000232234
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Allergic Activities of a New Benzopyranopyridine Derivative Y-12,141 in Rats

Abstract: Passive cutaneous anaphylaxis (PCA) mediated in rats by IgE-like antibodies against egg albumin or the benzylpenicilloyl determinant was inhibited in a dose-dependent manner by intravenous treatment with Y-12,141; the ED50 was 0.09–0.2 mg/kg. The inhibitory effect of Y-12,141 on PCA was about 5 times as potent as that of disodium cromoglycate (DSCG). Oral treatment with Y-12,141 resulted in the inhibition of PCA, showing an ED50 of 2.5 mg/kg. This action of Y-12,141 on PCA was considered to be due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In addition, we found that Y-12,141 did not inhibit the antigen-antibody reaction (20). In these respects, Y-12,141 is different from DSCG and mepyramine.…”
mentioning
confidence: 70%
“…In addition, we found that Y-12,141 did not inhibit the antigen-antibody reaction (20). In these respects, Y-12,141 is different from DSCG and mepyramine.…”
mentioning
confidence: 70%
“…In addition, traxanox sodium has anti asthmatic activity (1,2). In adult chronic asthmatics, prednisolone can decrease the airway resistance and theophylline and iso proterenol can improve the arterial oxygen tension (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…A new synthetic compound, traxanox (9 chloro-5-oxo-7-(1 H-tetrazol-5-yl)-5H [1 ] benzopyrano- [2,3-b]pyridine) sodium penta hydrate has been shown to possess anti anaphylactic effects (1,2). This agent has also been shown to enhance the production of spleen and thymus-rosette forming cells in C57BL/6 mice (3), a lower responder to sheep red blood cells (SRBC), and to inhibit that in BALB/c mice (4), a higher responder mice to SRBC.…”
mentioning
confidence: 99%
“…In the previous papers, we have reported that Y-1 2,141 (9-chloro-5-oxo-7-(1 H tetrazol-5-yl)-5H- [1 ]benzopyrano [2,3-b] pyridine sodium salt pentahydrate, traxanox sodium pentahydrate**)…”
mentioning
confidence: 99%
“…The anti anaphylactic effect of this agent was sug gested to be due to an inhibition of release of allergic mediators such as histamine and slow reacting substance of anaphylaxis (1)(2)(3). Traxanox sodium has been suggested to have a capacity to suppress the IgE production in the BN rat (4) and to potentiate immune responses in dd mice immunized with low doses of sheep red blood cells (SRBC) (5).…”
mentioning
confidence: 99%